Deaths due to absence of an affordable antitoxin for plant poisoning - Eddleston, M.; Senarathna, L.; Mohamed, F.; Buckley, N.; Juszczak, E.; Sheriff, M.H.R.; Ariaratnam, C.A.; Rajapakse, S.; Warrell, D.; Rajakanthan, K. (My University, 2003)
There is a severe shortage of affordable antivenoms and antitoxins in the developing world. An anti-digoxin antitoxin for oleander poisoning was introduced in Sri Lanka in July, 2001, but because of its cost, stocks ran out in July, 2002. We looked at the effect of its introduction and withdrawal on case fatality, and determined its cost-effectiveness. The antitoxin strikingly reduced the case fatality; its absence resulted in a three-fold rise in deaths. At the present price of US2650 dollars per course, every life saved cost 10209 dollars and every life year cost 248 dollars. Reduction of the antitoxin's price to 400 dollars would reduce costs to 1137 dollars per life gained; a further reduction to 103 dollars would save money for every life gained. Treatments for poisoning and envenoming should be included in the present campaign to increase availability of affordable treatments in the developing world.